Existence Of (18,9;f)-Arc Of Type (4,9) In PG(2,5) - Makbola J (College of Education for Pure Sciences, 2007)
Abstract In this paper we prove the existence of (18,9;f)-arc of type (4,9) when L0 =13 in the projective plane of order five ,and classified it then give an example of this case .Then by personal computer we construct some projectively distinct (13,4)-arc in PG(2,5) and compare the results with (18,9;f)-arc of type (4,9) .Also this paper conclude the proves of the theorems that deduced.